Science and policy: an STS Approach of the path to a new international labour standard on biological hazards - Avendaño Antúnez, Pilar (The University of Edinburgh, 2024)
This research project reflects on the complex interplay between science and policy in negotiating a new International Labour Standard on biological hazards, utilising a Science and Technology Studies framework. The literature review critically examines the role of public engagement in science and policy, policy implementation strategies, and social movement unionism. The study aims to explore how different factors, such as epistemic and behavioural influences, and various contexts, including political background and available resources, affect negotiation processes and policy outcomes. The research incorporates qualitative methods of participant observation and semi-structured interviews conducted during the 112th International Labour Conference, supplemented by a scoping review of International Labour Organisation documents illustrated with examples from Argentina, the Dominican Republic, and Mexico. Findings acknowledge that public engagement significantly shapes policy outcomes in intricate and non-mutually exclusive dynamics. This empirical work concludes that social dialogue and policy implementation are still embedded in epistemic differentiation and interactions between science and public engagement, emphasising the importance of integrating knowledge(s) within policymaking to achieve equitable governance in current debates on Occupational Safety and Health. Finally, the study proposes a hybrid model of knowledge sharing to enhance interactions between science and policy in global governance.
Keywords: Science and Technology Studies (STS); International Labour Standard; Public engagement; Policy implementation; Knowledge sharing